Community and public culture the Marwaris in Calcutta, 1897-1997 - Hardgrove, Anne. (New York : Columbia University Press, 2007)
"This book explores the historical and cultural processes by which people under colonial and postcolonial rule come to regard themselves as part of a "community," sharing a particular local and panregional ethnic community identity. The focus of this ethnohistorical case study of community formation is a wealthy and controversial migrant business community in Calcutta, the Marwaris."--Preface.
Electronic text (HTML) and image data (JPG).
Mode of access: Intranet.
This volume is made possible by a grant from the Andrew W. Mellon Foundation.
Caption title; description based on screen of 2007-12-11.
Originally published by Gutenberg-e: www.gutenberg-e.org.
Includes bibliographical references.
Keywords: India -- Calcutta; India; Calcutta (India) -- Social life and customs; Marwaris; Caste